The Effect of Giving Pre-Test and Postest on Learning Outcomes of the AMIK Medicom Student Research Methods - Bena Ginting; Dinaria Sembiring (Enrichment : Journal of Management, 2020)
This study aims to determine the effect of giving a pre-test and post-test on the learning outcomes of AMIK MEDICOM student research methods. This study uses three variables consisting of one dependent variable, namely Learning Outcomes (Y), while the independent variable is Pre-Test (X1) Post-Test (X2). The type of research used is explanatory research through associative research, namely research that aims to explain the influence between two or more variables. In this study, the population is students of the Academy of Informatics and Medicom Computers with Informatics Management Study Program Level 2 (two) semester 4 who study at Jl. Land No. 74 Medan totaling 254. The sample in this study was 30% of the population, namely 76 people. The data collection method was done by using a questionnaire and literature study. Data analysis was performed by testing data quality (validity and reliability), classical assumption test, t test (partial test), F test (simultaneous test).